Peripheral blood eosinophil and classification of residual hematoma help predict the recurrence of chronic subdural hematoma after initial surgery - Chen, Sichao; Shao, Linqian; Ma, Li (Frontiers in Surgery, 2022)
Chronic subdural hematoma (CSDH) is a common type of intracranial hemorrhage in neurosurgical practice, whose incidence has increased markedly in recent years. However, CSDH still troubles clinicians with a high postoperative recurrence rate. The presence of eosinophils has been confirmed in some CSDH surgical specimens. Furthermore, postoperative residual hematoma has not been classified, and its association with the recurrence of CSDH remains unknown. The present study aimed to test the hypothesis that the peripheral blood eosinophils and the classification of postoperative residual hematoma are significant for the prediction of CSDH recurrence after burr-hole surgery. A retrospective review of 258 CSDH patients who received burr hole surgery in Sir Run Run Shaw Hospital, between 2015 and 2020, was performed. A complete blood picture with differential count was taken before surgery. Clinical, laboratory and radiographic factors predicting CSDH recurrence were identified in univariable and multivariable analyses. Univariable analysis showed that the percentage of eosinophils, peripheral blood eosinophil count<0.15 × 109/L, gradation and separated types, postoperative volume of the residual cavity≥70ml, residual air volume≥28ml, residual hematoma volume≥55ml, residual hematoma width≥1.4cm, postoperative midline shift≥5.6mm, postoperative brain reexpansion rate<41%, postoperative low-density type and postoperative high-density type correlated with the recurrence of CSDH. Multivariable analysis, however, showed that peripheral blood eosinophil count<0.15 × 109/L, gradation and separated types, preoperative midline shift≥9.5mm, postoperative brain reexpansion rate<41%, postoperative low-density type, and postoperative high-density type are independent predictors for the recurrence of CSDH. We expect that peripheral blood eosinophils and the classification of postoperative residual hematoma may facilitate our understanding of the recurrence of CSDH after initial surgery.